2014
DOI: 10.1039/c4lc00042k
|View full text |Cite
|
Sign up to set email alerts
|

Droplet optofluidic imaging for λ-bacteriophage detection via co-culture with host cell Escherichia coli

Abstract: Bacteriophages are considered as attractive indicators for determining drinking water quality since its concentration is strongly correlated with virus concentrations in water samples. Previously, bacteriophage detection was based on a plague assay that required a complicated labelling technique and a time-consuming culture assay. Here, for the first time, a label-free bacteriophage detection is reported by using droplet optofluidic imaging, which uses host-cell-containing microdroplets as reaction carriers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 25 publications
(24 reference statements)
0
28
0
Order By: Relevance
“…177 However, the need to create an aerosol prior to detectionmass spectrometry requires the input of sample ions in the gas phasewith these two methods precludes the use of a two-phase system wherein cells can be encapsulated preaerosol formation. 128 In a label-free analogue to the work from ref. 204 Direct optical detection is more readily integrated into microfluidic systems, given the transparent nature of the materials typically used (glass, PDMS, PMMA, etc.…”
Section: Single-cell Emulsions By Sortingmentioning
confidence: 99%
“…177 However, the need to create an aerosol prior to detectionmass spectrometry requires the input of sample ions in the gas phasewith these two methods precludes the use of a two-phase system wherein cells can be encapsulated preaerosol formation. 128 In a label-free analogue to the work from ref. 204 Direct optical detection is more readily integrated into microfluidic systems, given the transparent nature of the materials typically used (glass, PDMS, PMMA, etc.…”
Section: Single-cell Emulsions By Sortingmentioning
confidence: 99%
“…In optofluidic research, the advanced on-chip flow cytometry is usually divided into two optical categories: one is detected by the traditional far-field scattering light [45][46][47] and the other is detected by the near-field evanescent wave 48,49 . For example, Yu et al reported a cytometer to detect bacteriophage by the far-field scattering light and droplet optofluidic imaging (Fig.…”
Section: Biochemical Samples Manipulation and Sensing In Flowing Liquidsmentioning
confidence: 99%
“…For example, Yu et al reported a cytometer to detect bacteriophage by the far-field scattering light and droplet optofluidic imaging (Fig. 5(b)) 47 . The sample alignment on both vertical and horizontal direction was realized by the flexible 3D hydrodynamic.…”
Section: Biochemical Samples Manipulation and Sensing In Flowing Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various microfluidic devices have been introduced for the study of cell cultivation and high-throughput screening (Shen et al 2014); (Falconnet et al 2011). Diverse methods of droplet generation and droplet capture have been developed to monitor cell growth (Jakiela et al 2013;Yu et al 2014). In this study, a low-cost oil and surfactant combination that was stable under high temperature (50 °C) was developed.…”
Section: Introductionmentioning
confidence: 99%